Youth Emigration from the Southeast Europe : Reasons and Motivations - Ostrý, Michal (2022)
The emigration of young people is an important topic in most of the South European (SEE) countries. To help understand why young people are leaving, I construct eight factors of aspirations, motivations, and values of a unique representative sample of 10 000 respondents from 10 SEE countries. Then I use the cluster analysis to group them and see if they differ in their migration intentions. I am able to differentiate 4 clusters which together have 68 % of the youth population from the region, which show a significant difference to the mean in their intention to migrate.